2011
DOI: 10.1016/j.joca.2011.01.018
|View full text |Cite
|
Sign up to set email alerts
|

IL-17RA aptamer-mediated repression of IL-6 inhibits synovium inflammation in a murine model of osteoarthritis

Abstract: Our results suggest that RA10-6 can inhibit synovial inflammation by blocking IL-17/IL-17RA-mediated IL-6 expression. RA10-6 acted synergistically with celecoxib to inhibit IL-6 expression in synovial tissues. Thus, aptamers targeting IL-17RA might serve as potent adjunctive agents for the early treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 33 publications
(23 reference statements)
0
36
0
Order By: Relevance
“…In vivo activity has been shown using a DNA L-selectin aptamer to block lymphocyte trafficking [50], multimeric OX40 or CD28 aptamers to enhance the potency of a DC-based vaccine and tumor immunity [51,52], and an IL17RA aptamer injected into inflamed joints to reduce arthritis [53,54]. The first in vivo example of using aptamers to overcome checkpoint blockade showed that a multivalent CTLA-4 aptamer (tetramer of a 35 nt aptamer linked to an adapter) could inhibit CTLA-4 and enhance tumor immunity in mice comparably to CTLA-4 antibody [55].…”
Section: Immunological Applications Of Aptamers For In Vivo Immune Cementioning
confidence: 99%
“…In vivo activity has been shown using a DNA L-selectin aptamer to block lymphocyte trafficking [50], multimeric OX40 or CD28 aptamers to enhance the potency of a DC-based vaccine and tumor immunity [51,52], and an IL17RA aptamer injected into inflamed joints to reduce arthritis [53,54]. The first in vivo example of using aptamers to overcome checkpoint blockade showed that a multivalent CTLA-4 aptamer (tetramer of a 35 nt aptamer linked to an adapter) could inhibit CTLA-4 and enhance tumor immunity in mice comparably to CTLA-4 antibody [55].…”
Section: Immunological Applications Of Aptamers For In Vivo Immune Cementioning
confidence: 99%
“…28 IL-17 mediated transduction leads to further activation and expression of pro-inflammatory cytokines such as IL-1, IL-6, and IL-8 that contribute to the inflammation. A strong correlation between the expression of IL-17 and IL-15 was observed in the SFs of RA patients but not in OA patients.…”
mentioning
confidence: 99%
“…For the MTT assay, L929 cells treated with scFv2-CH/CL/hIL-1β proliferated at a much faster rate than those treated with Diabody-CH/CL/hIL-1β, but remarkably slower than cells treated with hIL-1β alone. Some studies have reported that IL-17A induces the release of IL-8 and IL-6 [30]. We identified that IL-6 and IL-8 of Diabody-CH/CL/hIL-17A-treated HeLa cells were lower than that of scFv2-CH/CL/hIL-17A-treated cells.…”
Section: Discussionmentioning
confidence: 66%